Green apps in action: how motivational forces shape intention to use - Lim, Xin Jean; Cheah, Jun Hwa; Cheah, Isaac (John Wiley and Sons, 2025)
As environmental challenges escalate, recycling behavior has become a critical sustainability strategy, with green applications (green apps) gaining prominence as transformative tools in modern markets. Despite their growing relevance, the interaction of intrinsic and extrinsic motivational factors influencing green app adoption remains underexplored. Grounded in self-determination theory, this study examines the direct, indirect, and contingent drivers of green app adoption. Data were collected from 584 participants in China using two complementary research designs: a cross-sectional survey and an experimental study. The findings reveal that users' attitudes are positively shaped by intrinsic motivators, including perceived sense of accomplishment and willingness to sacrifice. Extrinsic factors, including information quality and service quality, also exert significant influence, while the impact of gamified rewards is contingent on users' biospheric values. This study advances theoretical understanding by illuminating the dynamic interplay between intrinsic and extrinsic motivations in environmental technology adoption. For practitioners, the results offer actionable strategies for designing and marketing green apps tailored to user motivations, thereby fostering recycling behaviors and advancing sustainability through innovative digital solutions.